Report of 25th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2004)
Hội nghị lần thứ 25 của Tổ chức liên nghị viện ASEAN được tổ chức tại Phnom Penh, Campuchia từ ngày 12-17 tháng 9 năm 2004.